Pola Komunikasi Dalam Rangka Menjaga Solidaritas Antar Anggota Badan Eksekutif Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik Di Universitas Bhayangkara Surabaya - Tri Prasetijowati; Crist Diva Sudona; Fierda Nurany (FISIP UWP, 2023)
An organization is a place for a group of people who work together in a rational and systematic manner that is guided or controlled to achieve certain goals using the resources available in it. One of the goals of organizing for students is to improve communication skills. This is because communication skills are very important in the world of work and daily activities. In every organization will have a goal that hopefully will be realized through each member in it. So also with BEM FISIP Bhayangkara University Surabaya. Therefore, good communication is needed to maintain solidarity and a sense of togetherness in each member so that the goals of the organization can be achieved. This research was conducted to analyze communication patterns to maintain the solidarity of each member applied to the organization. The research method used is descriptive qualitative using purposive sampling approach. The informants were nine people consisting of the chairman, deputy, KOMINFO division, MSDM division, MINBAT division, and academic division and three active members of BEM FISIP. The result is that there are several efforts made to maintain solidarity between members, namely through the form of activities by conducting face-to-face meetings such as Meetings, New Student Orientation Period, Organizational Training, Watching together, Sports, Social Services and through social media. So that every member of BEM FISIP Bhayangkara University Surabaya maintains solidarity in their organization